Knowledge of Parkinson’s disease among non-PD specialists: a web-based survey in South China - Lyu, Shaohua; Li, Zhe; Mao, Zhenhui; Sun, Jingbo; Zheng, Chunye; Su, Qiaozhen (Frontiers in Aging Neuroscience, 2025)
BackgroundParkinson’s disease (PD) is a prevalent, disabling neurodegenerative disorder. Early diagnosis and treatment of PD remains challenging due to the absence of definitive diagnostic tests and the non-specificity of its clinical manifestations. Initial consultations for PD symptoms often involve specialists who are not specifically trained in PD. Consequently, it is imperative to assess the general knowledge regarding PD among these specialists to develop optimal educational strategies and enhance early recognition and diagnosis of PD.MethodsWe developed a questionnaire covering motor symptoms, non-motor symptoms, prodromal symptoms, risk factors and antiparkinsonian medications based on published guidelines, and conducted the web-based survey via Wenjuan xing (https://www.wjx.cn/) among physicians not specializing in PD in Guangdong Province, China.ResultsA total of 312 respondents, working in 28 diverse departments across 64 hospitals of three different categories, were eligible for data analysis. Notably, 95.2% of the respondents were aware of rest tremor as a motor symptom, yet only 76.9% recognized bradykinesia as a motor symptom. Regarding non-motor symptoms, erectile dysfunction, urinary dysfunction, restless legs, olfactory loss, orthostatic hypotension, rapid eye movement behavior disorder (RBD), lower back pain and diaphoresis, were recognized by less than 50% of the respondents. Additionally, with the exception of subthreshold parkinsonism or abnormal quantitative motor testing, prodromal symptoms such as excessive daytime somnolence, depression (± anxiety), olfactory loss, urinary dysfunction, RBD, and constipation were recognized by 36.5–48.7% of the respondents. First-degree relatives with PD received recognition from 86.5% of the respondents, whereas the remaining risk factors were recognized by 50–60% of the participants. Concerning protective factors for PD, recognition was limited to no more than 23%. Levodopa and dopamine releasers were the most widely recognized antiparkinsonian medications, while the recognition of other medications was below 70%. Variables such as medical degrees, professional titles, hospital categories, and education subjects contributed to statistical differences in PD knowledge.ConclusionAmong non-PD specialists in south China, current knowledge regarding PD, including non-motor symptoms, prodromal symptoms, risk and protective factors, and antiparkinsonian medications, is relatively inadequate. This necessitates targeted education and training to improve their understanding and recognition of PD.